Plastic powder coating methods [Plasti̇k toz kaplama yöntemleri̇] - (:unkn) unknown (My University, 1999)
Adding decorative, mechanical or wear properties to materials through the surface modification have been among the aims of human beings since very early times. Surface modifications and surface coatings and specific properties which substrates do not have them. It is possible to get new materials, which are suitable for some specific purposes, out of cheap and easily produced materials only by chancing surface properties of substrates. Plastic powder coatings are widely used since they are generally highly resistant to corrosion, UV light, water, bases and acids. In this study plastic powder coating methods will be dealt with. Plastic powder coating methods are as follows; dipping, fluidized bed, electrostatic coating, flame spray and plasma spray coatings.
Keywords: Coating; Plastic; Powder; Surfaces